Dimensions of justice & justification in EU and transnational contexts - Herlin-Karnell, Ester (Discussion Papers / Wissenschaftszentrum Berlin für Sozialforschung, Center for Global Constitutionalism, 2015)
This discussion paper is part of a series of contributions to the conference "Towards a Grammar of Justice in EU Law", which took place on 6-7 November 2014 at VU University Amsterdam, sponsored by ACCESS EUROPE Amsterdam, VU Centre for European Legal Studies and the Dutch Research Council VENI grant. The introduction to this special issue presents the contributions and explains the main idea behind this collection of papers. Specifically, the special issue explores a grammar of justice and justification through political theory, legal and sociological perspectives and discuss their relevance in EU and transnational governance. In addition, this introduction links the papers together and supplies some concluding thoughts. (author's abstract)